Stent Placement Across the Renal Vein Inflow in Patients Undergoing Venous Reconstruction Preserves Renal Function and Renal Vein Patency: Experience in 93 Patients. (April 2019) - Chick, Jeffrey Forris Beecham; Gemmete, Joseph J.; Hage, Anthony N.; Bundy, Jacob J.; Brewerton, Charles; Fenlon, Jordan B.; Abramowitz, Steven D.; Coleman, Dawn M.; Srinivasa, Ravi N.; Williams, David M.
Purpose: To determine if stent placement across the renal vein inflow affects kidney function and renal vein patency.Methods: Between June 2008 and September 2016, 93 patients (mean age 39 years, range 15–70; 54 women) with iliocaval occlusion underwent venous stent placement and were retrospectively reviewed. For this analysis, the patients were separated into treatment and control groups: 51 (55%) patients had suprarenal and infrarenal iliocaval venous disease requiring inferior vena cava stent reconstruction across the renal vein inflow (treatment group) and 42 (45%) patients had iliac vein stenting sparing the renal veins (control group). Treatment group patients received Wallstents (n=15), Gianturco Z-stents (n=24), or suprarenal and infrarenal Wallstents such that the renal veins were bracketed with a "renal gap" (n=12). Stenting technical success, stent type, glomerular filtration rate (GFR), and creatinine before and after stent placement were recorded, along with renal vein patency and complications.Results: All procedures were technically successful. In the 51-patient treatment group, 15 (29%) patients received Wallstents and 24 (47%) received Gianturco Z-stents across the renal veins, while 12 (24%) were given a "renal gap" with no stent placement directly across the renal vein inflow. In the control group, 42 patients received iliac vein Wallstents only. Mean prestent GFR was 59±1.8 mL/min/1.73 m 2 and mean prestent creatinine was 0.8±0.2 mg/dL for the entire cohort. Mean prestent GFR and creatinine values in the Wallstent, Gianturco Z-stent, and "renal gap" subgroups did not differ from the iliac vein stent group. Mean poststent GFR and creatinine values were 59±3.3 mL/min/1.73 m 2 and 0.8±0.3 mg/dL, respectively. There were no differences between mean pre- and poststent GFR (p=0.32) or creatinine (p=0.41) values when considering all patients or when comparing the treatment subgroups and the control group. There were no differences in the poststent mean GFR or creatinine values between the Wallstent (p=0.21 and p=0.34, respectively) and Gianturco Z-stent (p=0.43 and p=0.41, respectively) groups and the "renal gap" group. One patient with a Wallstent across the renal veins developed right renal vein thrombosis 7 days after the procedure.Conclusion: Stent placement across the renal vein inflow did not compromise renal function. A very small risk of renal vein thrombosis was seen.